Extra Virgin Olive Oil meningkatkan Ekpresi Reseptor Estrogen Î± Dan Ketebalan Endometrium Rattus Norvegicus yang Dipapar Rhodamin B - Ita Noviasari (Journal of Ners and Midwifery, 2018)
Rhodamin B is harmful to the body because it is proven can increase the oxidative stress on various reproductive chain. Rhodamin B contains compounds of chlorine (Cl), is dangerous and halogen compounds are reactive. Damage to the hypothalamus will interfere with the secretion of FSH and LH cause the follicle ripening so distracted that result in a decrease in the hormone estrogen. The hormone estrogen plays an important role in the menstrual cycle and proliferation of the endometrium. This research aimed to prove the effect of Extra Virgin Olive Oil (EVOO) with the expression of estrogen receptors Î± and endometrial thickness of Rattus norvegicus exposed by rhodamin B. The design used true experimental with an approach of post test only control group design. The research used white rat (Rattus norvegicus wistar strain) as the sample. The results showed that EVOO could become an alternative to prevent oxidative stress due to exposure of rhodamin B.